Antiviral activity of amiodarone in SARS-CoV-2 disease - Bílek, R; Danzig, V; Grimmichová, T (Physiological research, 2022)
Amiodarone seems to exhibit some antiviral activity in the disease caused by SARS-CoV-2. Here we have examined the SARS-CoV-2 disease course in the entire population of the Czech Republic and compared it with the course of the disease in patients treated with amiodarone in two major Prague's hospitals. In the whole population of the Czech Republic SARS-CoV-2 infected 1665070 persons (15.6 %) out of 10694000 (100 %) between 1 April 2020 and 30 June 2021. In the same time period only 35 patients (3.4 %) treated with amiodarone were infected with SARS-CoV-2 virus out of 1032 patients (100 %) who received amiodarone. It appears that amiodarone can prevent SARS-CoV-2 virus infection by multiple mechanisms. In in-vitro experiments it exhibits SARS-CoV-2 virus replication inhibitions. Due to its anti-inflammatory and antioxidant properties, it may have beneficial effect on the complications caused by SARS-CoV-2 as well. Additionally, inorganic iodine released from amiodarone can be converted to hypoiodite (IO-), which has antiviral and antibacterial activity, and thus can affect the life cycle of the virus.
Keywords: Antiviral Agents; Humans; amiodaron; Amiodarone; lidé; antivirové látky; SARS-CoV-2; antibakteriální látky; Anti-Bacterial Agents; COVID-19